Playing hide and seek: Tumor cells in control of MHC class I antigen presentation. (August 2021) - Jongsma, M.L.M.; Neefjes, J.; Spaapen, R.M.
Highlights: Multiple new players in the MHC class I antigen presentation pathway were recently identified. Tumor cells escape from CD8 + T cell recognition by modulating the MHC class I pathway. Research to reversible modulation of antigen presentation provides targetable immunotherapeutic options. Abstract: MHC class I (MHC-I) molecules present a blueprint of the intracellular proteome to T cells allowing them to control infection or malignant transformation. As a response, pathogens and tumor cells often downmodulate MHC-I mediated antigen presentation to escape from immune surveillance. Although the fundamental rules of antigen presentation are known in detail, the players in this system are not saturated and new modules of regulation have recently been uncovered. Here, we update the understanding of antigen presentation by MHC-I molecules and how this can be exploited by tumors to prevent exposure of the intracellular proteome. This knowledge can provide new ways to improve immune responses against tumors and pathogens.